Factors Influencing the Foreign Language Learning Quality: A Study at a Cooperative Education Unit (SPK) School in Surabaya - Yuliana Lianto; Zeplin Jiwa Husada Tarigan; Ricky Ricky (Petra International Journal of Business Studies, 2022)
This research examines the correlation between the Native-Speaking Foreign Language Teachers' Professional Competencies, Teaching Methods, and Attitude Towards Learning in the Foreign Language Learning Quality in a Cooperation Education Unit or Satuan Pendidikan Kerjasama (SPK) in Surabaya. This quantitative research involved 144 students from the fourth, fifth, and sixth grades as the respondents or research participants. The data of this research were analyzed using the Partial Least Square (PLS) on SmartPLS 3.0 application. The results show that the Native-Speaking Foreign Language Teachers' Professional Competencies significantly influenced Teaching Methods. Furthermore, Teaching methods significantly influenced the Attitude Towards Learning, while the Attitude Towards Learning significantly influenced Foreign Language Learning Quality. Teaching Methods have also proven to be a mediator in the influence of Attitude Towards Learning (VAF=0,1965 or 19,65%). Based on the research findings, schools and teachers need to emphasize the professional competencies of native-speaking foreign language teachers and teaching methods to improve the quality of foreign language learning.